Needs of STEAM Education in Elementary Classes (Grades 6–8) in Pakistan: A Systematic Review (2023-2025) - Muhammad Rafiq-Uz-Zaman (Universitas Negeri Surabaya, 2026)
Pakistan elementary education needs Grade 6-8 to be important in cultivating STEAM (Science, Technology, Engineering, Arts, Mathematics) ability. Nonetheless, there are system-wide issues like inapt teacher training, curriculum that does not align well with STEAM, lack of resources, and weak enforcement of policy, that prevent serious immediate integration of STEAM courses. This systematic review will seek to find evidence-based interventions to enhance STEAM education in these grades in the Pakistani education setting. In accordance with the PRISMA 2020 standards, searches in Scopus, Web of Science, ERIC and Google Scholar were performed in the period between March and August 2025 in order to find peer-reviewed articles that published after 2023-2025. Syntheses at the regional and global levels were also taken into account (2013-2023). The keywords used included Pakistan, Grades 6-8, and STEAM/STEM and were combined with the keywords that included curriculum, professional development, assessment, and policy. Among 345 records found, 28 articles were reviewed in their full-text, which resulted in the selection of 18 primary studies and 15 contextual sources (n=33). Quality assessment was done using the Mixed Methods Appraisal Tool (MMAT) and Critical Appraisal Skills Program (CASP). Ten major themes were identified, such as alignment of curriculum with national standards, practice-based teacher development, inquiry-based pedagogy, computational thinking, inclusive design and career awareness related to math self-efficacy. Blending of genuine arts and economical technology infrastructure was addressed as a key to the success. The effective implementation of STEAM must be multilevel, that is, it has to be coordinated through policy interventions at the curriculum level in terms of curriculum guides, teacher training, equitable provision of resources, and career awareness programs. To achieve equal results, it is necessary to use the principles of Universal Design to Learning and digital competence development pathways. The analysis was limited by scarcity of Pakistan-specific studies and language as well as heterogeneity among studies made meta-analysis impossible. Successful STEAM learning in Grades 6-8 in Pakistan needs interventions on the curriculum, pedagogy, professional development, assessment, and policy, which are comprehensive and coordinated. It is possible that there is a possibility of successful integration, but further specific research on Pakistan is required.